2013
DOI: 10.4028/www.scientific.net/aef.8-9.103
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Natural Clays Catalysts on Thermal Degradation of a Plastic Waste Mixture

Abstract: Abstract. The thermal and catalytic degradation of a plastic wastes mixtures using two types of natural clays catalysts has been carried out in order to obtaining liquid oils with potential use in the chemical industry. Thus, the polymer waste mixture (PWM) of polystyrene (PS), poly(ethylene terephthalate) (PET) and poly(vinyl chloride) (PVC) were thermally degraded at 420 °C in absence and presence of studied catalysts in mass ratio 1:10, catalyst/PWM. The catalysts were characterized by N 2 adsorption-desorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For example, Filip et al investigated the thermal degradation processes at 420 °C of a plastic waste mixture (PS + PET + PVC) in the absence and presence of two types of natural Romanian clay catalysts [ 65 ]. The GC-MS results showed that the liquid fractions contained mainly monoaromatic compounds.…”
Section: Catalytic Activity Of Mixed Natural Claysmentioning
confidence: 99%
“…For example, Filip et al investigated the thermal degradation processes at 420 °C of a plastic waste mixture (PS + PET + PVC) in the absence and presence of two types of natural Romanian clay catalysts [ 65 ]. The GC-MS results showed that the liquid fractions contained mainly monoaromatic compounds.…”
Section: Catalytic Activity Of Mixed Natural Claysmentioning
confidence: 99%